Ways and means of research method - Kumar M., Dileep; Mohd Noor, Nor Azila (Research India Publications, 2013)
Number of books have come out with research tools and technique.While concentrating developing countries and in par with their knowledge and skill very few books are tailor made.Start with the concepts, differentiating the methods, fine tuning the knowledge regarding research with process, tools and techniques, incorporated in this book make a reader or scholar simple enough to capture the meaning and its applicability.Pursuing a research topic, or arriving at managerial decisions, with accompanying proof and evidences also need the support of tools and techniques for authenticity and accountability This book is an art and learning for any scholar or professional who wants to be investigative, critical, logical and scientific in their decision making and inferences leading to policy and project implementation.The “ways and means of research methods” incorporated in this book will equip the readers, researchers and professionals with scientific knowledge, critical mindset, and logical conclusions in an efficient and effective way.I presume this book titled ““ways and means of research methods”” will extend better insight and understanding of research and research methodology to the managers, teachers and professionals, researchers and student community.